HUBUNGAN PENGETAHUAN DAN PERILAKU VAGINAL HYGINE DENGAN KEJADIAN KEPUTIHAN PADA REMAJA PUTRI DI SMA KARTINI BATAM - Acholder T Perdoman Sirait; Nopri Esmiralda; Ance Purnama (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Vaginal discharge is a common condition experienced by young women and can be physiological or pathological. The main factor that contributes to the incidence of vaginal discharge is knowledge and vaginal hygiene behavior. This study aims to determine the relationship between the level of knowledge and vaginal hygiene behavior and the incidence of vaginal discharge in adolescent girls at SMA Kartini Batam. Methods: This research uses quantitative methods with a cross-sectional design. The research sample consisted of 129 female students selected using simple random sampling techniques. Data was collected using a structured questionnaire and analyzed using the Chi-Square test. Results: The results showed that the majority of respondents had a good level of knowledge (94.6%) and good vaginal hygiene behavior (62%). Pathological vaginal discharge was found in 56.6% of respondents. Bivariate analysis showed that there was no significant relationship between knowledge and the incidence of vaginal discharge (p-value = 0.110). However, there is a significant relationship between vaginal hygiene behavior and the incidence of vaginal discharge (p-value = 0.000). Conclusion: The conclusion of this study is that although a good level of knowledge is not directly related to the incidence of vaginal discharge, poor vaginal hygiene behavior increases the risk of pathological vaginal discharge. Keywords: Knowledge, Behavior, Vaginal Hygiene, Vaginal Discharge